Transforming EFL Classroom Practices and Promoting Students’ Empowerment: Collaborative Learning From a Dialogical Approach - Janeth Juliana Contreras León; Claudia Marcela Chapetón Castro (Profile Issues in Teachers' Professional Development, 2017)
This study investigates the impact of implementing collaborative learning from a social and dialogical perspective on seventh graders’ interaction in an English as a foreign language classroom at a public school in Bogotá, Colombia. Thirty students participated in this action research where field notes, questionnaires, semi-structured interviews, and artifacts of students’ work were used to collect data during a complete academic year. Results show that taking a critical approach to language education and understanding collaborative learning as a social construction of knowledge can ignite opportunities for changing traditional teaching and learning practices where both the teacher and students take different roles, thus balancing classroom relations and interaction among participants and also promoting students’ empowerment.